Risk factors for dislocation after revision total hip arthroplasty: A systematic review and meta-analysis. (February 2017) - Guo, Lele; Yang, Yanjiang; An, Biao; Yang, Yantao; Shi, Linyuan; Han, Xiangzhen; Gao, Shijun
Abstract: Background: No formal systematic review or meta-analysis was performed up to now to summarize the risk factors of dislocation after revision total hip arthroplasty(THA). Aims: The present study aimed to quantitatively and comprehensively conclude the risk factors of dislocation after revision total hip arthroplasty. Methods: A search was applied to CNKI, Embase, Medline, and Cochrane central database (all up to October 2016). All studies assessing the risk factors of dislocation after revision THA without language restriction were reviewed, and qualities of included studies were assessed using the Newcastle–Ottawa Scale. Data were pooled and a meta-analysis completed. Results: A total of 8 studies were selected, which altogether included 4656 revision THAs. 421 of them were cases of dislocation occurred after surgery, suggesting the accumulated incidence of 9.04%. Results of meta-analyses showed that age at surgery (standardized mean difference −0.222; 95% CI -0.413–0.031), small-diameter femoral heads (≤28 mm) (OR 1.451; 95%CI 1.056–1.994), history of instability (OR 2.739; 95%CI 1.888–3.974), number of prior revisions ≥ 3 (OR, 2.226; 95% CI, 1.569–3.16) and number of prior revisions ≥ 2 (OR 1.949; 95% CI 1.349–2.817), acetabular components with elevated rim liner were less likely to develop dislocation after revision THA (OR 0.611; 95% CI 0.415–0.898). Conclusions: Related prophylaxis strategies should be implemented in patients involved with above-mentioned risk factors to prevent dislocation after revision THA. Highlights: Many risk factors have been identified for the dislocation following revision THA. However, these factors are still undergoing controversial or have been not been well summarized. Constrained liner, trochanteric osteotomy, Cup inclination, cup anteversion, BMI, single component revision were not found to be risk factors. History of instability and prior revisions are the most consistently significant risk factors for dislocation after revision THA.